Suriname : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report, 2018)
Suriname is recovering from the deep recession of 2015-16. Growth has turned positive, inflation has reduced to single digits, real interest rates have turned positive, and the external position has on balance strengthened. Nonetheless, the economy remains heavily dependent on the mineral sector, and faces fiscal, monetary, and banking sector vulnerabilities.